2017
DOI: 10.5937/jpea1702081a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spinach and chickpea flour fortification on cooking, functional and textural properties of wheat pasta

Abstract: The present study was led to prepare pasta from wheat instead of semolina and effect of spinach powder and chickpea flour fortification on cooking, functional and textural properties pasta was assessed. Cooking losses were more in spinach wheat (SW)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this sample, the hardness was 1.18 times higher than hardness of control sample. Increasing the hardness of pasta has been reported by increasing the protein content (Alireza Sadeghi & Bhagya, 2008; Bhatt, Jatav, Kiledar, & Srivastava, 2015; Shyam et al., 2017; Wee, Loud, Tan, & Forde, 2019). Teterycz et al (2020) reported that by increasing the protein content, the hardness of pasta increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sample, the hardness was 1.18 times higher than hardness of control sample. Increasing the hardness of pasta has been reported by increasing the protein content (Alireza Sadeghi & Bhagya, 2008; Bhatt, Jatav, Kiledar, & Srivastava, 2015; Shyam et al., 2017; Wee, Loud, Tan, & Forde, 2019). Teterycz et al (2020) reported that by increasing the protein content, the hardness of pasta increased.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, by combining cereals with legumes, a complete profile of proteins in pasta can be achieved (Duranti, 2006). Various legumes such as peanut (Howard & Hung, 2010), faba (Laleg et al., 2017), chickpea (Kore, 2018; Shyam, Mishra, Vaidya, & Sharma, 2017), and soybean (Marengo et al., 2018) have been used in numerous studies to improve the nutritional value of pasta.…”
Section: Introductionmentioning
confidence: 99%